Problem-Based Learning and Direct Learning Models Influence Learning Outcomes on Basic Soft Ball Game Techniques given Critical Thinking Ability - Dirgantara, I Made; Lanang Agung Parwata, I Gusti; Iwan Swadesi, I Ketut (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2024)
Several factors, including monotonous learning models and critical thinking skills, cause low PJOK learning outcomes. This research aims to analyze problem-based and direct learning models on the learning outcomes of basic softball game techniques in terms of necessary thinking skills. The research uses a 2X2 treatment by level design. The population is 115 people. A sampling of 60 people was selected using a purposive sampling technique. Data collection method using tests. The analysis technique uses data from two-way ANOVA, followed by an independent sample t-test. The results show that the learning outcomes for the softball game of students who follow the problem-based learning model are higher than those who follow the direct learning model. There is an interaction between the learning model and critical thinking skills in softball game learning outcomes. Students with high necessary thinking skills who follow the problem-based learning model have higher learning outcomes than those who follow direct learning, and students with low necessary thinking skills who follow the problem-based learning model have lower learning outcomes than those who follow explicit learning. This research concludes that the problem-based learning model influences learning outcomes regarding critical thinking abilities. This research implies that teachers can apply the PBL model to improve student learning outcomes.